2019
DOI: 10.1002/mgg3.664
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of expression of IL‐18, IL‐1β genes in the articular joint by sumac fruit extract (Rhus coriaria L.)

Abstract: Background Osteoarthritis is the most common malignant disease in the world. The disease is caused by changes in the metabolism, the structure and function of multiple joints, and joint tissues. Sumac is one of the indigenous plants of Iran and has traditionally been used as a spice in Iran. The aim of this study was to investigate the reduction of expression of IL‐18, IL‐1β genes in the articular joint by sumac fruit extract (Rhus coriaria L.). Methods The alcoholic extract of sumac fruit (E.E.R.C.L) was prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Momeni et al were among the first to show a potential anti-inflammatory activity of Rhus coriaria . The authors demonstrated that sumac fruit alcoholic extract significantly reduced the level of mRNA of the pro-inflammatory cytokines IL-18 and IL-1β, in lipopolysaccharide-stimulated synoviocyte extracted from joint and fluid of limb of the 8-month-old healthy calf [ 122 ]. In another study, Gabr et al .…”
Section: Pharmacological and Biological Activities Of Rhmentioning
confidence: 99%
“…Momeni et al were among the first to show a potential anti-inflammatory activity of Rhus coriaria . The authors demonstrated that sumac fruit alcoholic extract significantly reduced the level of mRNA of the pro-inflammatory cytokines IL-18 and IL-1β, in lipopolysaccharide-stimulated synoviocyte extracted from joint and fluid of limb of the 8-month-old healthy calf [ 122 ]. In another study, Gabr et al .…”
Section: Pharmacological and Biological Activities Of Rhmentioning
confidence: 99%
“…Momeni et al. (2019) have reported that R. coriaria fruit extract reduced the expression of IL‐18, IL‐1 genes in the articular joint in healthy calf, using the real‐time PCR method. Results indicates that after the expression of IL‐18 cytokines, IL‐1 β increased to 100 %, and following the treatment with the alcoholic extract, the reduction of expression of these cytokines was 33.61 % and 29.01 %, respectively.…”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…It has been reported that alcoholic extract of R. coriaria fruit significantly reduced the level of mRNA of the pro-inflammatory cytokines IL-18 and IL-1β, in lipopolysaccharide-stimulated synoviocytes extracted from joint and fluid of limb of the 8-month-old healthy calf. 49 Previous studies showed similar results in terms of its anti-inflammatory activity using the carrageenan-induced foot oedema model. An example is the use of Rhus toxicodendron and the methanol extract of Rhus tripartita, which showed significant inhibition of inflammation in the carrageenan-induced foot oedema model.…”
Section: Evaluation Of Hind Paw Oedemamentioning
confidence: 56%